2013
DOI: 10.1016/s0924-9338(13)76541-6
|View full text |Cite
|
Sign up to set email alerts
|

1528 – Factors associated with physical domestic violence against women in countries of eastern mediterranean region (emr); a systematic review

Abstract: IntroductionPhysical domestic violence (DV) against women is associated with adverse health effects and great burden on victims, families and communities. The phenomenon, though prevalent in EMR countries, is not well defined regarding the determining factors.Objectives & aimsThis systematic review is to sum up evidences from the EMR countries, on factors associated with physical DV.Methods:Data sourcesPubmed, EMBASE, ISI, PsycInfo, IMEMR, Ovid, Global health, Cochrane Library, IranMedex, SID, IranDoc, Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The incidence rate of domestic violence against women in different Iranian cities ranges from 17.5% to 93.6%, making such act a major factor in physical and psychological damage to women (DeJong, Jawad, Mortagy, & Shepard, 2005). Some studies showed that 43.7% of women in Iran have been exposed to domestic violence at least once and experience it throughout the course of their married lives (Davoudi, Rasoulian, Ahmadzad Asl, & Nojomi, 2013). Some researchers in Iran found that the most prevalent type of domestic violence is emotional violence, followed by physical and sexual violence (81.8%, 8.41%, and 4.40%, respectively; Dolatian, Shams, Alavi Majd, & Moafi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of domestic violence against women in different Iranian cities ranges from 17.5% to 93.6%, making such act a major factor in physical and psychological damage to women (DeJong, Jawad, Mortagy, & Shepard, 2005). Some studies showed that 43.7% of women in Iran have been exposed to domestic violence at least once and experience it throughout the course of their married lives (Davoudi, Rasoulian, Ahmadzad Asl, & Nojomi, 2013). Some researchers in Iran found that the most prevalent type of domestic violence is emotional violence, followed by physical and sexual violence (81.8%, 8.41%, and 4.40%, respectively; Dolatian, Shams, Alavi Majd, & Moafi, 2012).…”
Section: Introductionmentioning
confidence: 99%